Peningkatan Pemahaman Hukum tentang Tindak Pidana Pencucian Uang bagi Karyawan di Sektor Perbankan - Anshar; Muhammad Taufiq La Ode; Adhyaksa, Andika Adhyaksa (Swadaya: Jurnal Pengabdian Masyarakat, 2025)
This Community Service Program aims to enhance the legal awareness of bank employees, helping them understand their rights and obligations while ensuring compliance with regulations to prevent money laundering and related banking offenses. With the theme Enhancing Legal Understanding on Money Laundering Crime Prevention for Bank Employees in Ternate City, this program is conducted through legal counseling in the form of lectures and discussions. In addition to educating participants on the characteristics of money laundering crimes, it also produces a journal article and an educational poster registered as Intellectual Property with the Directorate General of Intellectual Property (Dirjen HKI).The program has successfully increased bank employees' enthusiasm for understanding and identifying potential money laundering activities, as reflected in their active discussions and inquiries.